Portfolio mix of SLR : a study on treassury & FI operations of BRAC Bank Limited - Rahim, Md. Abdur (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.